The association between disclosures on control system over financial reporting and mechanisms of corporate governance: Empirical evidence from Germany and Poland - Jacek Gad (International Journal of Management and Economics, 2020)
The aim of the research was to determine the impact of selected corporate governance mechanisms on the scope of disclosures related to control system over financial reporting in Poland and Germany. The research group comprised of companies from the Warsaw WIG 30 index and the German DAX index in 2013. The disclosures were measured by the number of detailed disclosures about control system over financial reporting presented by the surveyed companies. The research results indicate that selected corporate governance mechanisms affect the scope of disclosures regarding the system of control over financial reporting. It was found that the number of supervisory board committees and the number of meetings of the supervisory board have a significant positive influence on the scope of disclosures regarding control over financial reporting. But, the increase in number of meetings of the audit committee has a significant negative impact on the scope of disclosures regarding control over financial reporting. The results of the research also indicate the role of national determinants of the scope of disclosures. The study was a comparative one nature and was conducted among companies from developed and developing capital markets.
Keywords: M41; G34; 650; corporate governance; control system; voluntary disclosure; financial statements